SPECIFIC PROPHYLAXIS OF INFLUENZA - Masharipova , Shakhista (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Influenza is one of the most widespread infectious diseases worldwide and has a significant impact on public health and the economy. This study evaluated the effectiveness and immunogenicity of seasonal influenza vaccination. During the 2023–2024 influenza season, a total of 122 participants were enrolled and divided into two groups: vaccinated (62 individuals) and control (60 individuals). The results demonstrated that the incidence of influenza, influenza-like illness, and related complications was significantly lower in the vaccinated group. Immunological analysis revealed a significant increase in antibody titers. The vaccination was found to be safe and well tolerated.